Digital Inclusion in Universities and Librarians’ Performance of Library Tasks During Covid-19 Pandemic in Nigeria - Unuabor, Stanley Omondiale; Ogbomo, Monday Obaidjevwe (Communicate: Journal of Library and Information Science, 2023)
The purpose of the study is to examine digital inclusion in universities and librarian’s performance of library tasks in the Covid-19 pandemic era in Nigeria. The scope of the study is the government owned University libraries, that is, State and Federal institutions within the six states in South-South, Nigeria. Literatures were reviewed in line with the variables under study. Correlational type of survey research design was adopted for this study, while the data collected was analyzed using descriptive and inferential statistics (that is, mean and standard deviation) to answer research questions. The criterion mean was placed at 2.50. For Hypothesis one Pearson Product Moment Correlation Co-efficient was used. A total of 223 librarians across University libraries in South-South Nigeria made up the population of the study. The entire population (total enumeration) was used as the sample size which was considered adequate for the study. Questionnaire was used for data collection. A total of 223 copies of the questionnaire were distributed and 183 were found usable, representing 82% response rate. Consequently, the following finding were made. The level of digital inclusion in Universities for librarian’s performance of library tasks in the Covid-19 pandemic era in South-South, Nigeria is high. The level of access to digital technologies in Universities for librarian’s performance of library tasks in the Covid-19 era in South-South, Nigeria is high etc. Due to the findings of the study, recommendations which include that: The level of digital inclusion in Universities for librarian’s performance of library tasks in South-South, Nigeria should be sustained. The contribution to knowledge include that, the study has established the level of digital inclusion in Universities libraries for librarian’s performance of library tasks in the Covid-19 pandemic era in South-South, Nigeria to be low.